2012
DOI: 10.1021/bi301282k
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Analysis of the cAMP/Protein Kinase A Signaling Pathway

Abstract: To define the proteins whose expression is regulated by cAMP and protein kinase A (PKA), we used a quantitative proteomics approach in studies of wild-type (WT) and kin- (PKA-null) S49 murine T lymphoma cells. We also compared the impact of endogenous increases in the level of cAMP [by forskolin (Fsk) and the phosphodiesterase inhibitor isobutylmethylxanthine (IBMX)] or by a cAMP analogue (8-CPT-cAMP). We identified 1056 proteins in WT and kin- S49 cells and found that 8-CPT-cAMP and Fsk with IBMX produced dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…6, a and b), having similar volume density, number and size of mitochondria, and cristae abundance (Table 3), consistent with the health and protection from damage by the reactive oxygen species of kin Ϫ cells (15). These data also suggest that the decreased rates of maximal respiration in kin Ϫ cells (Figs.…”
Section: Electron Microscopy and Mitochondrial Morphology Of Wt And Kinsupporting
confidence: 77%
See 3 more Smart Citations
“…6, a and b), having similar volume density, number and size of mitochondria, and cristae abundance (Table 3), consistent with the health and protection from damage by the reactive oxygen species of kin Ϫ cells (15). These data also suggest that the decreased rates of maximal respiration in kin Ϫ cells (Figs.…”
Section: Electron Microscopy and Mitochondrial Morphology Of Wt And Kinsupporting
confidence: 77%
“…The current mitoproteomic analysis identified 2013 proteins, whereas our previous proteomic study of lysates from WT and kin Ϫ S49 cells identified 1056 proteins (15); 469 proteins were in common between these studies. The greater number of proteins identified in this study may result from the use of iTRAQ 4-plex in place of 8-plex (51).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…cAMP/PKA signaling in immature T cells is apoptotic but has other functional roles, including in metabolism and stress responses. Because kin -cells are devoid of cAMP/PKA signaling, they respond differently to oxidative and metabolic stress (50,51).…”
Section: Pka-riα Protein Expression Is Prominently Decreased In Kin -mentioning
confidence: 99%